2005
DOI: 10.1165/rcmb.2004-0322oc
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Peptide Transporter PEPT2 in Primary Cultures of Human Upper Airway Epithelium

Abstract: This study characterizes the expression and function of the peptide transporter hPepT2 (SLC15A2) in differentiated primary cultures of human upper airway lung epithelia obtained from six human donors. Genotype analysis of a SNP in exon 15 of hPepT2 genotypes in six donors revealed an expected distribution of the two main variants present at similar frequency (two AA homozygotes, two BB homozygotes, and two AB heterozygotes). Real-time PCR analysis of the hPepT2 mRNA message revealed no significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
4
22
1
Order By: Relevance
“…It has also been reported that bacterial pore-forming toxins, which insert into host membranes, may aid in Nod1 ligand delivery into the host cytosol (64). Additionally it has been shown that host cells express peptide transporters that can transport both Nod1 and Nod2 ligands directly into the host cytosol (2,78).…”
Section: Host Sensing Of Peptidoglycan and Modified Peptidoglycanmentioning
confidence: 99%
“…It has also been reported that bacterial pore-forming toxins, which insert into host membranes, may aid in Nod1 ligand delivery into the host cytosol (64). Additionally it has been shown that host cells express peptide transporters that can transport both Nod1 and Nod2 ligands directly into the host cytosol (2,78).…”
Section: Host Sensing Of Peptidoglycan and Modified Peptidoglycanmentioning
confidence: 99%
“…Lung cell culture was conducted as previously described (9). and maintained in a 1:1 mixture of Dulbecco's modified Eagle's media (DMEM) and Ham's F12 media (DMEM/F12) (Invitrogen, Carlsbad, CA) supplemented with 2% Ultroser G and antibiotics at 378C, and 5% CO 2 .…”
Section: Lung Cell Isolation and Cell Culturementioning
confidence: 99%
“…All transport experiments were performed as described previously (9). The culture inserts with hLECs were washed three times and conditioned for 2 hours with 0.2 ml apical (pH 5 6.5) and 0.4 ml basal transport buffer (BL) (pH 5 7.4).…”
Section: Transport Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pept2 mRNA is expressed in specific cell types of the brain, including astrocytes, subependymal cells, and ependymal cells, and Pept2 protein is detected along the apical membrane of epithelial cells of the choroid plexus (Table 5) (Berger and Hediger, 1999;Shu et al, 2002). Pept2/PEPT2 mRNA and/or protein are also expressed in the enteric nervous system, colon, liver, pancreas, lungs, nasal mucosa, and mammary glands (Groneberg et al, 2001(Groneberg et al, , 2002Zhang et al, 2004a;Bahadduri et al, 2005;Ruhl et al, 2005;Lu and Klaassen, 2006;Quarcoo et al, 2009).…”
mentioning
confidence: 99%